The Use of Artificial Neural Network for Prediction of Dissolution Kinetics - Elcicek, H.; Akdogan, E.; Karagoz, S. (HINDAWI LTD, 2014)
Colemanite is a preferred boron mineral in industry, such as boric acid production, fabrication of heat resistant glass, and cleaning agents. Dissolution of the mineral is one of the most important processes for these industries. In this study, dissolution of colemanite was examined in water saturated with carbon dioxide solutions. Also, prediction of dissolution rate was determined using artificial neural networks (ANNs) which are based on the multilayered perceptron. Reaction temperature, total pressure, stirring speed, solid/liquid ratio, particle size, and reaction time were selected as input parameters to predict the dissolution rate. Experimental dataset was used to train multilayer perceptron (MLP) networks to allow for prediction of dissolution kinetics. Developing ANNs has provided highly accurate predictions in comparison with an obtained mathematical model used through regression method. We conclude that ANNs may be a preferred alternative approach instead of conventional statistical methods for prediction of boron minerals.
Keywords: LEACHING KINETICS; ULEXITE; COLEMANITE; TEMPERATURE; PERFORMANCE; POWER; ORE; Science & Technology - Other Topics